The Correlation Self-Acceptance and Compliance Haemodialysis Therapy in Patients with Chronic Kidney Disease - Erni Tri Indarti; Tunik Ambarwati (Master of Public Health Program Universitas STRADA Indonesia, 2023)
Patients with chronic kidney disease require long-term haemodialysis therapy. Patients who are unable to accept themselves tend to feel disappointed because they feel they are a burden on the family, so patients do not comply with regular haemodialysis therapy. The purpose of this study was to determine the relationship between self-acceptance and adherence to undergoing haemodialysis in patients with chronic kidney disease in the Haemodialysis Room of Nganjuk Hospital. The design of this research is correlation with cross sectional approach. The research was carried out on 14-19 November 2022 in the Haemodialysis Room of the Nganjuk Hospital. The population of this study were all patients with chronic kidney disease undergoing haemodialysis in the Haemodialysis Room of Nganjuk Hospital, totaling 40 patients. Samples were taken by purposive sampling technique and 28 respondents were obtained. The independent variable was self-acceptance and the dependent variable was adherence to undergoing haemodialysis. The data collection instrument used a questionnaire and data analysis used the Contingency Coefficient test with α = 0.05. The results of the Contingency Coefficient test yielded a p-value = 0.031 ≤ α (0.05), there is a relationship between self-acceptance and adherence to undergoing haemodialysis in patients with chronic kidney disease in the Haemodialysis Room of Nganjuk Hospital. Chronic Kidney Disease Patients with good self-acceptance will have the ability to cope with anxiety, depression and feelings of hopelessness, so that patients are motivated to recover from their illness.